Combined Snail and E-cadherin Predicts Overall Survival of Cervical Carcinoma Patients: Comparison Among Various Epithelial-Mesenchymal Transition Proteins - Tian, Yuejun; Qi, Ping; Niu, Qian; Hu, Xuemei (Frontiers in Molecular Biosciences, 2020)
Background: Activation of Snail and synergistic loss of E-cadherin are hallmark features of the epithelial-mesenchymal transition (EMT), which contributes to the metastasis phenotype of epithelial cancer cells. However, the prognostic impact of Snail and of its combination with E-cadherin and with other EMT prognostic markers has not yet been systematically studied in cervical carcinoma. This study aimed to explore the prognostic value of combined Snail and E-cadherin in patients with cervical carcinoma and compared it to the prognostic value of other EMT prognostic markers. Methods: We retrospectively identified every initial diagnosis of cervical carcinoma among 203 patients treated at our hospital in China from January 2008 to March 2013. We examined the prognostic significance of Snail and other EMT protein markers, such as E-cadherin, Slug, ZEB1, Twist, Vimentin, and Survivin, by univariate and multivariate survival analyses. Results: Multivariate analyses showed that Snail and E-cadherin were significant biomarkers for overall survival (OS) in cervical carcinoma patients (HR, hazard ratio = 1.744, P = 0.036 and HR = 1.738, P = 0.047; respectively). Moreover, a combined index including Snail and E-cadherin showed enhanced prognostic value compared to that of Snail or E-cadherin alone. The present data demonstrate that Snail shows a negative correlation with E-cadherin (P < 0.001). High Snail expression and low E-cadherin expression were also more common in high tumor stages (P = 0.044 and P = 0.036; respectively) and lymph node metastasis (both P < 0.001). Moreover, Snail was a superior prognosis factor compared to Slug, ZEB1, Twist, Vimentin, and Survivin in cervical carcinoma. Conclusion: Based on our results, Snail and E-cadherin may be considered as independent prognosis markers, and the combination of Snail and E-cadherin might improve the OS prediction accuracy for patients with cervical carcinoma.